Comparison of cervical vertebrae MRI image information between axial T2 Fse and T2 propeller sequences - Husna, Melati Amelia; Susanto, Fani; Fitriana, Lutfatul; Supriyadi, Supriyadi; Samudra, Alan (Science Midwifery, 2025)
Examinations performed on MRI of cervical vertebrae take a long time and cause patients to feel uncomfortable during the examination. FSE is a technique that can be used to produce fast examination times. Patient discomfort can also cause movement during the examination, which can cause artifacts in the resulting images. These movements can be minimized with the PROPELLER technique. This study is quantitative using an experimental method with a sample size of 15 volunteers who were each scanned with T2 FSE and T2 PROPELLER sequences. This study was conducted using a questionnaire in which each image produced was evaluated by 2 radiology specialist observers using the visual grading analysis (VGA) method to assess each anatomy of the corpus vertebrae, intervertebrae disc, spinal cord, CSF, intraforamen structure, nerve root and artifacts. The statistical results showed that the image quality of T2 FSE and T2 PROPELLER sequences had ap value of 0.000 (p<0.05). The sequence has a difference, namely T2 PROPELLER produces more detailed image quality on anatomy and pathology, and can reduce the occurrence of artifacts due to movement in the cervical area, and T2 FSE produces less informative image quality due to artifacts. In addition, there are differences in MRI scanning time of cervical vertebrae T2 FSE sequences which are faster than T2 PROPELLER and T2 PROPELLER is good at reducing artifacts.